Brominated flame retardants extraction from waste electrical and electronic equipment-derived ABS using supercritical carbon dioxide. (15th July 2021) - Gripon, Layla; Belyamani, Imane; Legros, Benoît; Seaudeau-Pirouley, Karine; Lafranche, Eric; Cauret, Laurent
Highlights: Temperature and pressure impact on the extraction efficiency were determined. Granulometry of the sample had an influence on the extraction efficiency. The maximum extracted bromine was 43.5 ± 0.9% using supercritical CO2 . The addition of ethanol as a co-solvent improved the extraction rate. Abstract: Persistent organic pollutants such as brominated flame retardants represent a major problem in the end-of-life of polymer materials. This study investigates the extraction of brominated flame retardants (BFR) from real waste electrical and electronic equipment (WEEE) using supercritical carbon dioxide ( sc -CO2 ). Sc -CO2 is a non-toxic solvent which possesses intermediate properties between liquids and gases which confer it high diffusivity and solubility. A batch of WEEE-derived acrylonitrile–butadienestyrene (ABS) was first characterized to determine its bromine and BFR composition which was found to be four times higher than the regulation limit set in 2019. Then, different parameters of the sc- CO2 process such as temperature, pressure, granulometry and the use of a co-solvent were studied to estimate the effect of each one on the BFR extraction efficiency. With the view to determine the recyclability of the treated polymer, the impact of the extraction process on the polymer material was also studied by Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC) and Size Exclusion Chromatography (SEC). The extraction process performed on <500 µm particle size sample at 40 °C and 500 bars during 6 h and using ethanol as a co-solvent allowed to remove 43.5 ± 0.9% of bromine, which was the maximum extraction rate obtained. Sc- CO2 extraction was found to be an efficient technique to remove tetrabromobisphenol A (TBBPA) but the tested conditions did not allow to remove enough polybromodiphenylethers (PBDE) to satisfy the regulation. Sc- CO2 process seems to be a promising pre-treatment method prior to mechanical recycling as no degradation effect on the polymer matrix was observed.